Preparatory study for carbon sequestration modelling of agroforestry systems in Hungary: The assessment of the yield class distribution of windbreaks - Kiraly, Eva; Borovics, Attila (Acta Agraria Debreceniensis, 2024)
The escalating carbon dioxide emissions leading to global climate change are acknowledged as a paramount environmental challenge in the twenty-first century. The significance of land use systems in stabilising carbon dioxide levels and enhancing carbon sink potential has gained noteworthy attention from both the scientific and political communities. The Intergovernmental Panel on Climate Change emphasises that agroforestry systems present vital prospects for synergising climate change adaptation and mitigation efforts, offering substantial technical mitigation potential. Windbreaks are well-known agroforestry systems in Hungary and form an important part of agricultural landscapes. The improved agroforestry subsidy system in our country makes it relevant to model the carbon sequestration potential of windbreaks. In the framework of the ForestLab project we plan to develop a carbon sequestration model specific for Hungarian agroforestry systems. In this study, as a preparatory step of the model development, we assessed the yield class distribution of Hungarian windbreaks by tree species group and identified variables that had significant effect on yield class based on the data of the National Forestry Database. Our results show that among the examined effects the most important predictor of the yield class of windbreaks was the tree species group, followed by the thickness of the productive soil layer and the hydrology of the site.